The Role of Oxygen in ECM remodeling - Abzan, Nadia; Versey, Zoya; Willmore, William; Mostaco-Guidolin, Leila (CMBES Proceedings, 2024)
The extracellular matrix (ECM) regulates several cellular functions via different signals. The structure and composition of the ECM change in various diseases. The mechanisms of ECM alternations and the role of oxygen in ECM remodeling is poorly understood. We are establishing in vitro models that simulate the ECM microenvironment to investigate the effect of oxygen in ECM remodeling.